The role of voluntary work in alleviating psychological stress among the military retirees in Bethlehem governorate - Adawi, Lubna Muhammad (Journal of Educational and Psychological Sciences, 2022)
The aim of this study is to identify the role of voluntary work in alleviating psychological stress among the military retirees in Bethlehem governorate and its relationship to a range of variables including gender, age, academic qualification, and years of experience, place of residence, military rank, and income level for retirees. The population of the study consisted of (158) retired, while the sample of the study consisted of (138) retired, which represent 87.3%. The results of the study: 1. The role of voluntary work in alleviating the psychological pressure of military retirees has reached a high level. The psychological dimension has reached the highest average of the psychological impact of the military retirees, the social dimension, the family dimension, the health dimension and the family dimension. 2. There were statistically significant differences in the average of voluntary work in alleviating psychological stress among the military retirees in Bethlehem Governorate due to the gender variable in favor of females, where the mean of them was 4.64, while the male average was 4.24. In light of the results of the study، the researcher recommended several recommendations، including: Work on a strategic plan to establish community clubs and institutions that support the presence of military retirees and provide them with activities within their work. Preparing military and community training programs for retirees to ensure their contribution to cultural and social awareness.